Rationally Designed TiO2 Nanostructures of Continuous Pore Network for Fast‐Responding and Highly Sensitive Acetone Sensor. Issue 12 (15th October 2021) - Suh, Jun Min; Cho, Donghwi; Lee, Sangmin; Lee, Tae Hyung; Jung, Jae‐Wook; Lee, Jinho; Cho, Sung Hwan; Eom, Tae Hoon; Hong, Jung‐Wuk; Shim, Young‐Seok; Jeon, Seokwoo; Jang, Ho Won
Abstract: For the last several years, indoor air quality monitoring has been a significant issue due to the increasing time portion of indoor human activities. Especially, the early detection of volatile organic compounds potentially harmful to the human body by the prolonged exposure is the primary concern for public human health, and such technology is imperatively desired. In this study, highly porous and periodic 3D TiO2 nanostructures are designed and studied for this concern. Specifically, extremely high gas molecule accessibility throughout the whole nanostructures and precisely controlled internecks of 3D TiO2 nanostructures can achieve an unprecedented gas response of 299 to 50 ppm CH3 COCH3 with an extremely fast response time of less than 1s. The systematic approach to utilize the whole inner and outer surfaces of the gas sensing materials and periodically formed internecks to localize the current paths in this study can provide highly promising perspectives to advance the development of chemoresistive gas sensors using metal oxide nanostructures for the Internet of Everything application. Abstract : Highly sensitive and selective detection of CH3 COCH3 by 3D TiO2 is achieved by systematically designed highly periodic and porous nanostructures. The promising gas sensing characteristics can be attributed to extremely high gas molecule accessibility to the bottom region of 3D TiO2 and sensitive electrical modulation upon adsorption and desorption of target gas achieved by precise control of the interneck thickness.